Playce-making: transformation of space in a participatory game design project within a Canadian junior high school - Baradaran Rahimi, Farzan (My University, 2022)
When we give meanings to a physical space, we engage in place-making. With technologies, the place-making activities can be extended to virtual and hybrid spaces. In games, actual or virtual space can gain narrative and meaning transforming into a playce (i.e., a place for play). We suggest that playce-making (i.e., transforming a space into a playce) activities in the classroom may provide adolescents with a rich learning context for teamwork, problem-solving, and knowledge creation. In our study, we observed ninth graders’ engagements in game design projects at a Canadian suburban school. We discuss how learners created their own learning paths in transforming the actual space of their school, conceptually and typologically, into hybrid and virtual playces. Our research indicates that the typological transformation of space motivates learners to create or adopt narratives meaningful to them and their community from familiar spaces.
Keywords: Place-making; transformation of space; participatory design; game design; junior high school